Prevention of hepatitis with immunoglobulin. Issue 549 (July 1971) - Reid, Daniel
Abstract : Immunoglobulin appears to be effective in preventing the clinical features of infectious hepatitis among contacts of the disease provided it is given before the later stages of the incubation period. A single dose of 750 mg gives protection for a period of up to 7 months. The evidence of the value of immunoglobulin for contacts of serum hepatitis is conflicting.